New Travelling Wave Solution of Burgers Equations - John, Zainab; Abbas, Basim Akhudir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, we studied the travelling wave solving for some models of Burger’s equations. We used sine-cosine method to solution nonlinear equation and we used direct solution after getting travelling wave equation.